Shocks, Stocks, and Rocks: Precious Metals as Safe Haven in Crises for Equity Market in South-East Asian Tri-nation - Yudha Ari Wijaya; Powell Gian Hartono; Elia Ardyan (Vifada Management and Social Sciences, 2026)
Purpose: Southeast Asian equity markets face recurring crises in which cross-asset correlations rise and diversification weakens. Evidence on the joint defensive roles of gold, silver, platinum, and palladium for the equity markets of Indonesia, Singapore, and Malaysia remains fragmented. Research Design and Methodology: This study evaluates the hedge and safe-haven properties of gold (XAU), silver (XAG), platinum (XPT), and palladium (XPD) for the Jakarta Composite Index (JKSE), the Straits Times Index (STI), and the Kuala Lumpur Composite Index (KLCI) using daily data from July 1st, 2005 to June 30th, 2025, divided into two sub-periods. Metals are priced in domestic currency, trading days are synchronized, and returns are computed as log differences. GARCH(1,1) models estimated under Gaussian, generalized error distribution, and Student-t innovations are combined with quantile regression (τ = 0.10–0.50) to capture tail dependence. Findings and Discussion: Results indicate that XAU is the only metal consistently hedging the three indices, evidenced by negative average coefficients, while its safe-haven role is state-dependent, strengthening during specific distress episodes. XAG, XPT, and XPD exhibit positive co-movement even at low quantiles, consistent with diversification or pro-cyclicality. Implications: The findings reinforce safe-haven status as regime- and tail-dependent and support gold as an adaptive crisis overlay in ASEAN equity risk management.